Identifying Competitive Advantages of Gas Turbine Generators in MOPU: Maleo Field Case Study - Aditya Permana Putra; Tony Antonio (Journal of Economics and Management Scienties, 2026)
This study examines whether implementing a Gas Turbine Generator (GTG) on a Mobile Offshore Production Unit (MOPU) at the Maleo Field, operated by Supraco Lines, can create a competitive advantage. The research is driven by anticipated field development involving gas and condensate, presenting an opportunity to optimize internal energy resources and decrease reliance on diesel-based power generation. A qualitative case study methodology was employed, utilizing semi-structured interviews, non-participant observation, and document analysis. Six purposively selected informants contributed expertise in engineering, offshore installation management, departmental leadership, procurement, health, safety, and environment, and academic strategy. Data analysis involved coding, data reduction, data display, conclusion drawing, and source triangulation, guided by the Resource-Based View and VRIO framework. The results indicate that GTG implementation can create strategic value by reducing dependence on diesel logistics, enhancing operational reliability, lowering emissions, and increasing maintenance efficiency. The rarity of this advantage arises from the unique combination of GTG technology, gas-condensate availability, and offshore MOPU operational conditions. Barriers to imitation include platform constraints, technical modifications, safety requirements, and accumulated operational knowledge. Organizational support is demonstrated through cross-functional coordination, operator competence, adaptation of standard operating procedures, monitoring, maintenance planning, and risk governance. In summary, GTG represents a potential source of sustainable competitive advantage and supports adaptive offshore operations and a sustainability-oriented business strategy.